Mystery of Ancestral Land: The Traces of King Tawang Alun in Macan Putih - Daud Hizbalhaq Addamawi; Siti Zuhrotul Amelia; Ahmad Ali Munazat (SINGOSARI, 2026)
The purpose of this paper is to analyze the influence of Hindu-Buddhist culture that entered and developed in the society of the Archipelago. The method used includes field observations and literature studies obtained through a review of books, journals, and various reports related to this paper. This paper discusses the historical legacy of the Kingdom of Blambangan, the relics of King Tawang Alun in Macan Putih. It aims to gain an understanding of the origins, roles, and physical conditions of the site, as well as how Hindu-Buddhist culture has influenced the society in the Archipelago. Through activities such as Napak Tilas, the younger generation is motivated to preserve this cultural heritage. Another part of this paper focuses on the relics of King Tawang Alun II, a historical site of the Macan Putih kingdom in Java, which attracts tourists and followers of the Kejawen belief. Although many ancient artifacts have been found, the lack of maintenance has caused these historical items to be sold or destroyed. Additionally, to provide a direct picture of this site, this research will conduct interviews with caretakers and analyze various historical sources. The research method we use in this study is the historical research method, with several data collection techniques including observation, and direct interviews with sources who have knowledge about the macan putih site. With support from visitors and donors for preservation, various efforts have been made to improve this site and provide modern facilities that will satisfy visitors. This article uses a qualitative method with a literature study that includes an analysis of several journals related to the site and King Tawang Alun. This article provides a good overview of the impact of pilgrimage sites and their implications as a driving factor for tourists to visit. Furthermore, this article is intended to provide a comprehensive review of the history, impact, and maintenance conditions of this site. The results of this research show how visitors undertake pilgrimages for their respective purposes, and while there is good preservation, it is carried out independently from donations provided by visitors, and the lack of government support poses a potential loss of historical value.